The Role of Busines Actors in Ensuring Halal Products - Qahar Awaka, Muhammad; Rachmawati, Rachmawati; Lolita, Lolita; Yaniza, Tiza (JURNAL USM LAW REVIEW, 2023)
The number of certified halal products from business actors in the area of the South Pontianak Sub-district tends to be low. This study aimed to determine the role of business actors in implementing halal product guarantees in the South Pontianak city area with the title of the role of business actors in guaranteeing halal products in the South Pontianak sub-District area. This type of research is a qualitative approach using a juridical sociological system. The population in this study consists of business actors in the South Pontianak Sub-district area. Data collection techniques involved observation, interviews, and documentation techniques. The results of this study indicate that business actors in ensuring halal products in the South Pontianak sub-district area have not been optimally implemented as they experienced some obstacles; firstly, business actors are unaware of the obligation to register their products; secondly, the registration process for Halal certification is difficult and costly. The efforts made by business actors in ensuring halal products are by joining the MSME group, which assists in product registration, obtaining halal certificates, and receiving guidance and socialization from the government.